Clinical Reasoning in Occupational Therapy Practice: A Scoping Review of Qualitative and Conceptual Peer-Reviewed Literature. - da Silva Araujo, Angelica; Anne Kinsella, Elizabeth; Thomas, Aliki; Demonari Gomes, Laysla; Quevedo Marcolino, Tais (American Journal of Occupational Therapy)
Importance: The occupational therapy clinical reasoning literature includes a large proportion of peer-reviewed qualitative and conceptual articles. Although these articles can contribute to the understanding of how clinical reasoning has been conceptualized in occupational therapy, they have not yet received in-depth analytic attention. To address this gap, we conducted a scoping review. Objective: To examine how qualitative and conceptual literature has addressed clinical reasoning in occupational therapy. Data Sources: Database searches were conducted in Scopus, Web of Science, PsycINFO, Embase, and MEDLINE. Study Selection and Data Collection: Included articles were published between 2010 and 2019, were peer reviewed, addressed clinical reasoning in occupational therapy, were qualitative or conceptual articles, focused on practitioners, and were in English. Twenty-six articles met the inclusion criteria. Data were extracted according to relevant categories and were analyzed numerically and thematically. Findings: Four themes were identified: clinical reasoning processes, factors influencing clinical reasoning, new models or frameworks to guide clinical reasoning, and emergent perspectives on clinical reasoning. Conclusions and Relevance: This review advances knowledge about how clinical reasoning has been conceptualized in occupational therapy and has been applied in a range of practice contexts. The review highlights discussions about types of reasoning, the dynamic and iterative nature of reasoning, contextual dimensions of reasoning, client-centered and occupation-based approaches, new frameworks and models, and emergent and innovative perspectives on clinical reasoning in occupational therapy. What This Article Adds: This scoping review represents an important contribution to knowledge about how clinical reasoning has been conceptualized in occupational therapy by mapping key themes and illuminating scholarly conversations in the qualitative and conceptual clinical reasoning literature. This review advances knowledge about how clinical reasoning has been conceptualized in occupational therapy and has been applied in a range of practice contexts.